2018
DOI: 10.14738/assrj.512.5545
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Customer Satisfaction on Loyalty in the Ghana Banking Sector: The Effect of Trust Mediation

Abstract: Customer satisfaction, trust and loyalty have been extensively researched, but the continuous changing of customer needs and the changing banking regulatory environment necessitates a correspondingly continuous evaluation of these construct. This study analysed the impact that customer satisfaction has on customer loyalty. In addition, the study investigated the mediating role of trust in the relationship between customer satisfaction and customer loyalty. The study was conducted on 825 useable responses which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Additionally, CT significantly and favorably impacted CS and CL Morgan and Hunt's (1994) study found that CT positively impacted CS and CL. Banahene, Mensah, and Asamoah (2018) looked at how CS affected loyalty and how trust acted as a moderator. According to the study's findings, CS positively impacted loyalty both directly and indirectly via trust.…”
Section: Corporate Social Responsibilitymentioning
confidence: 99%
“…Additionally, CT significantly and favorably impacted CS and CL Morgan and Hunt's (1994) study found that CT positively impacted CS and CL. Banahene, Mensah, and Asamoah (2018) looked at how CS affected loyalty and how trust acted as a moderator. According to the study's findings, CS positively impacted loyalty both directly and indirectly via trust.…”
Section: Corporate Social Responsibilitymentioning
confidence: 99%
“…There is a direct correlation between customer satisfaction and customer loyalty. Due to the likelihood of making repeat purchases from the customer, the customer will be a loyal and satisfied customer (Banahene et al, 2018). With the lower price, a customer will start to believe that this certain brand is offering superior quality at a reasonable price, and as a result, they will begin to trust the brand, and thus he or she will become loyal to the brand (Yusuf et al, 2019).…”
Section: Relationship Between Customer Satisfaction and Customer Loyaltymentioning
confidence: 99%
“…Considering the evolutionary needs of banking customers in multiple contexts, marketing scholars (e.g. Albaity and Rahman, 2021;Banahene et al, 2018) argue that continuous research on the factors that impact trust and ultimately the future loyalty intentions of customers is required. Nkwede et al (2022) further argued the need to explore customer trust more in an African banking context in emerging markets.…”
Section: Introductionmentioning
confidence: 99%